2023
DOI: 10.1007/s10340-023-01693-7
|View full text |Cite
|
Sign up to set email alerts
|

Blue and UV light-emitting diodes (LEDs) disturb the greenhouse whitefly (Trialeurodes vaporariorum) from its host

Maria Athanasiadou,
Rainer Meyhöfer

Abstract: Push–pull strategy is a well-known and widely used technique for integrated pest management, leading to the reduction of insecticides. This strategy involves the use of mostly visual and chemical stimuli to repel pests from a valuable crop (push) and attract them to an appealing target, e.g., a trap, (pull). Based on former results, this study explored the effect of light-emitting diodes (LEDs) as repelling factors of whiteflies (push). Wavelengths of blue and ultraviolet (UV) were investigated in different li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…These results suggest that blue light can be used to develop environmentally friendly control strategies. For example, blue light has been applied to repel the whitefly T. vaporariorum from its host [41]. However, further research is still needed to promote the application of blue light irradiation in pest control, such as by combining blue light irradiation with insecticide control or pheromone-based mating disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that blue light can be used to develop environmentally friendly control strategies. For example, blue light has been applied to repel the whitefly T. vaporariorum from its host [41]. However, further research is still needed to promote the application of blue light irradiation in pest control, such as by combining blue light irradiation with insecticide control or pheromone-based mating disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Taking all aforementioned factors into account, conducting research on the response and consequence of insects to blue light irradiation will not only help us to understand blue-light-stress-related mechanisms, but can also provide ideas and theoretical support for the control of insect pests. A recent study has shown that blue and UV light can be used to distract the greenhouse whitefly (Trialeurodes vaporariorum) from its host [41].…”
Section: Introductionmentioning
confidence: 99%